Optical isotropization of anisotropic wurtzite Al‐rich AlGaN via asymmetric modulation with ultrathin (GaN)m/(AlN)n superlattices. Issue 4 (24th April 2013) - Lin, Wei; Jiang, Wei; Gao, Na; Cai, Duanjun; Li, Shuping; Kang, Junyong
<x xml:space="preserve">Abstract</x> Symmetric anisotropy in wurtzite semiconductors, e.g., AlGaN, has led to the significant optical anisotropy that is rather difficult to resolve. Here, a novel scheme for achieving optical isotropization in Al‐rich AlGaN through the introduction of additional asymmetric elements is demonstrated to compensate the native asymmetry. Asymmetric modulation of alloy composition and periodicity of (GaN)m/(AlN)n superlatices was proposed with first‐principles simulations. Results showed that the compensation for the c‐axial symmetry with the asymmetric ultrathin (GaN)m/(AlN)n superlatices (m ≤ 2) could well achieve the equivalence of the ordinary and extraordinary imaginary dielectric functions ε2 at the band edge. Measurement with spectroscopic ellipsometry for this (GaN)m/(AlN)n superlatice insertion in AlGaN host confirmed the theoretical predictions of the optical isotropization. This method can be transferred to other semiconductors in anisotropic structure and with troubles of optical anisotropy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>